Rapid Anisotropic Crystallization from Amorphous Bi₂Te₃ Thin Films by Microwave Annealing - K. Nakagawa; T. Iwamoto; I P. A. Karya; A. J. Muhammad; T. Asano; S. Mitsudo; T. Takizawa; M. Takashir (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
We investigated the crystallization behavior of amorphous Bi₂Te₃ thin films subjected to microwave annealing using both slow and rapid heating protocols. Films were deposited by RF magnetron sputtering and annealed with 2.45 GHz microwave irradiation. Slow annealing, performed under controlled temperatures below the melting point of Te, yielded randomly oriented polycrystalline films, whereas rapid annealing with high-power short pulses resulted in strongly c-axis-oriented crystallites. X-ray diffraction (XRD) analyses confirmed enhanced crystallinity and increased Lotgering factors under rapid annealing conditions. SEM observations showed minimal grain growth, suggesting that microwave irradiation promotes preferential orientation without significant grain coarsening. These results indicate that microwave annealing provides a unique, rapid, and effective method for directional crystallization of Bi₂Te₃ thin films, which could significantly enhance their thermoelectric performance.